2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346300
|View full text |Cite
|
Sign up to set email alerts
|

How stimulation speed affects Event-Related Potentials and BCI performance

Abstract: Abstract-In most paradigms for Brain-Computer Interfaces (BCIs) that are based on Event-Related Potentials (ERPs), stimuli are presented with a pre-defined and constant speed. In order to boost BCI performance by optimizing the parameters of stimulation, this offline study investigates the impact of the stimulus onset asynchrony (SOA) on ERPs and the resulting classification accuracy. The SOA is defined as the time between the onsets of two consecutive stimuli, which represents a measure for stimulation speed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 13 publications
(21 reference statements)
0
25
1
Order By: Relevance
“…Each tone had a length of 150 ms, followed by an inter stimulus interval (ISI) of 250 ms, thus the stimulus onset asynchrony (SOA) was 400 ms. The choice of the timing parameters was motivated by the results of previous studies which showed that the choice of stimulation speed is crucial for performance with auditory BCIs (Höhne and Tangermann, 2012 ; Käthner et al, 2013 ). Höhne and Tangermann ( 2012 ) tested SOAs between 50 and 1000 ms in a simple auditory oddball paradigm and found increasing P300 amplitudes with slower stimulation speed.…”
Section: Methodsmentioning
confidence: 99%
“…Each tone had a length of 150 ms, followed by an inter stimulus interval (ISI) of 250 ms, thus the stimulus onset asynchrony (SOA) was 400 ms. The choice of the timing parameters was motivated by the results of previous studies which showed that the choice of stimulation speed is crucial for performance with auditory BCIs (Höhne and Tangermann, 2012 ; Käthner et al, 2013 ). Höhne and Tangermann ( 2012 ) tested SOAs between 50 and 1000 ms in a simple auditory oddball paradigm and found increasing P300 amplitudes with slower stimulation speed.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the EP used a short SOA of 120 ms comprised by a brief yet supraliminal flash duration of 70 ms followed by a short inter-stimulus interval (ISI) of 50 ms, the time intervening between the flash termination and the onset of the next flash. In auditory ERP BCIs, Höhne and Tangermann found an individually optimized SOA preferable to fixed values [42]. Accordingly, this principle was extended from the auditory to the visual domain as an individually optimized SOA embodied within the EP in the present investigation.…”
Section: B Flashing Techniquesmentioning
confidence: 78%
“…Therefore, we designed to extend epoch interval to be 500 ms (namely EXP-3) relative to the Emotiv headset device in order to improve an accuracy of ERP patterns. As a result, there was a report of an individual choice of the matrix size and inter stimulus interval (ISI) [8] and stimulus onset asynchrony (SOA) [9][10] highly beneficial with respect to BCI performance. In order to segment the EEG according to the onset and epoch interval, we used the hardware trigger signal sent by EEG headset wirelessly.…”
Section: Experiments and Resultsmentioning
confidence: 99%